PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN LEARNING CYCLE 5E MODEL LORSCBACH KELAS V SEKOLAH DASAR - Akmal Rijal (Universitas Negeri Padang, 2017)
Learning tools that are used in the schools are still not optimal in facilitating the development of learners. The purpose of this study is to produce a device with a math learning 5E learning cycle model of Lorschbach valid, practical, and effective. This type of research is the development of research. The model used is a model development Plomp. The results showed that the study of mathematics by 5E learning cycle models developed Lorschbach have valid criteria in terms of content and construct. Practical learning device has been good in terms of enforceability, ease, and the time required. Learning device has also been effective in terms of activity and learning outcomes of students with an average value of learners activity increased and the level of mastery learning outcomes. This means learning devices effective in improving learning outcomes of students. Based on these results it can be concluded that the study of mathematics by 5E learning cycle Lorschbach models developed in the study of mathematics in class V SD can be declared valid, practical, and effective. Keywords: Learning tools, math, learning 5E learning cycle model of Lorschbach